BISHOP SEPTIMIUS FLORENCE TERTULLIANUS AND THE ISSUES OF HIS ERA - Fadel Lakhdar, (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the thought and influence of Bishop Septimius Florence Tertullianus within the context of the Roman Carthage during the second and third centuries ADs. Drawing on his extensive writings, this research analyses Tertullianus’s engagement with key social, moral, and religious issues of his time, including abortion, divorce, remarriage, public spectacles, and women’s adornment. It highlights his efforts to assert Christian doctrine in opposition to dominant pagan practices, revealing the complex dynamics among faith, society, and authority. The paper concludes that Tertullianus’s legacy lies in his rigorous defence of Christian values and his significant contribution to shaping early Christian identity in North Africa.